What do the dialysis patients of the Nuestra Señora de la Candelaria University Hospital think about the services received? Valuation of the quality perceived - Purificación Cerro López; Matani-Chugani Vinita; Antonio Carlos Santos Ruiz (Fundación para el Desarrollo de la Enfermería, 2008)
The following work tries to evaluate the satisfaction degree of the dialysis patients regarding the health attention received, and to identify the problems related to the health care services. To achieve this goal a qualitative-quantitative study was designed. The study population were patients who receive renal substitutive treatment in the Nuestra Señora de la Candelaria University Hospital (HUNSC). Quantitative data were collected by using the questionnaire (SERVQHOS) to 71% of the total population. Each item was punctuated in a Likert scale according to the degree of satisfaction (from 1 to 5). The SPSS 13.0 statistical program was used for the data analysis. Qualitative data were collected by formulating an open question which was answered on personal diaries written by some of these patients. The average global satisfaction obtained was 4. The professionalism of the sanitary personnel is among the better aspects valued (4.2) and the transport services among the worse valued (2.1). It was not found statistical significant relation between the analyzed variables and the patients satisfaction degree. Regarding the outcomes of the qualitative analysis, it contributes us very useful information to identify susceptible aspects to improve related to the medical and nursing attention, transport services, ward environment and other resources.